AKTA NOTARIS (AKTA OTENTIK) SEBAGAI ALAT BUKTI DALAM PERISTIWA HUKUM PERDATA - Tjukup, I Ketut; Siki Layang, I Wayan Bela; Martana, Nyoman A.; Markeling, I Ketut; Dananjaya, Nyoman Satyayudha; Arsha Putra, I Putu Rasmadi; Purnawan, Komang Widiana; Sari, Made Diah Sekar Mayang; Pundari, Ketut Nihan; Tribuana, Putu Ayu Ratih (Acta Comitas; Vol 1 No 2 (2016)DO - 10.24843/AC.2016.v01.i02.p05, 2016)
Notary is one of professions lawful services to public, which has responsibilities related with authentic attesting instruments, such as, letters,certificates, or documents made by him/her in written form concerning various lawful actions Departing from the circumstances as preventive measures of prevention needs to be premature given information about the notarial deed (deed authentic) as evidence in the event of civil law in order to later villagers in any transaction in a very large amount in order to carry out the agreement in front notary officials. The fact that occurs in the community, some of them are less aware of the importance of a document as evidence that an agreement between the parties is done with a sense of mutual trust and made ??orally, but there are also some people who understand the importance of making a document as evidence that the deal is made in writing, that it will be presented as a means of evidence.
Keywords: Notarial deed, Evidence